CHANGES IN WINTER WHEAT GROWN UNDER IRRIGATED AND RAINFED CONDITIONS - E. H. Rong; S.C. Li; Z. G. Zhao; M. C. Feng; C. Wang; M. J. Zhang; R. Li; R. Y. Wang; W. D. Yang (Journal of Animal and Plant Sciences, 2013)
Changes of the canopy spectral reflectance, leaf area index (LAI) and chlorophyll density (CHLD) of winter water in irrigated and dry land at different growth stage were studied to analyze the correlation between hyperspectral vegetation indices and CHLD, and to confirm the optimum vegetation indices for estimating CHLD of winter wheat in irrigated and dry land. The result showed the trend of changes in LAI similar to CHLD in irrigated and dry land, the values increased at first and then decreased, but the maximum value of CHLD and LAI appeared at different growth stages. The changes in canopy reflectance were also similar in irrigated and dry land, canopy reflectance formed an obvious reflection peaks at a waveband (510-680nm), but with the grain filling stage progressed, the reflection peaks gradually became unobvious, and disappeared at maturity. NDVI (780,670) might be better to predict CHLD of winter wheat in irrigated land, with the determination coefficient of 0.9451, but DVI (1200, 670) might be to predict CHLD of winter wheat in dry land, with the determination coefficient of 0.7346.
Keywords: Leaf area index; Chlorophyll density; Spectral parameters; Irrigated; Dry land